2019
DOI: 10.3390/nu11010163
|View full text |Cite
|
Sign up to set email alerts
|

A Boost in Mitochondrial Activity Underpins the Cholesterol-Lowering Effect of Annurca Apple Polyphenols on Hepatic Cells

Abstract: Reduction in cholesterol blood levels represents one of the therapeutic goals to achieve in order to reduce the occurrence of cardiovascular diseases. Commonly, this goal is attempted by promoting healthy lifestyle behaviors and low-fat diets. Recently, several nutraceuticals have been shown to possess cholesterol-lowering properties and are becoming common over the counter products. Among others, apple polyphenols efficiently lower total cholesterol levels in humans and impact overall lipid metabolism. Malus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 57 publications
0
33
0
Order By: Relevance
“…Other signaling pathways influenced by PACs involve cholesterol metabolism and catabolism. Under high fat intake, procyanidin B2 from Annurca apples reduces cholesterol synthesis by diverting citrate and acetyl-CoA to the Krebs cycle [ 319 ]. Concomitantly, it lowers fatty acid synthesis and promotes lipolysis and fatty acid β-oxidation thanks to a boost in mitochondrial activity [ 319 ].…”
Section: Pac Bioactivitymentioning
confidence: 99%
“…Other signaling pathways influenced by PACs involve cholesterol metabolism and catabolism. Under high fat intake, procyanidin B2 from Annurca apples reduces cholesterol synthesis by diverting citrate and acetyl-CoA to the Krebs cycle [ 319 ]. Concomitantly, it lowers fatty acid synthesis and promotes lipolysis and fatty acid β-oxidation thanks to a boost in mitochondrial activity [ 319 ].…”
Section: Pac Bioactivitymentioning
confidence: 99%
“…The intake of apples can significantly reduce the danger of lung cancer, particularly in women. Numerous diverse researches have observed that the apple is active in slowing down the oxidation of low-density lipoproteins [ 195 ]. Apple polyphenolic compounds improved the lifespan of fruit flies by 10%.…”
Section: Examples Of Polyphenolic-food: Anti-aging Super Foodmentioning
confidence: 99%
“…Rat brains were homogenized using a potter in 1 ml of pre-chilled methanol/water 1:1 solution, containing 10 nmol of internal standard, and centrifuged at 10,000 g for 10 min at 4 • C (Ser et al, 2015). The resulting supernatants were collected and transferred into Eppendorf tubes and stored at −80 • C. Analyses were performed according to a previous protocol (Sommella et al, 2019). Data were acquired on a SolariX XR 7T (Bruker Daltonics, Bremen, Germany).…”
Section: Mass Spectrometry-based Metabolomics Statistics and Analysismentioning
confidence: 99%